Digitalization of Islamic Finance in the 5.0 Era: A Systematic Review and Challenges in Strengthening the Halal Ecosystem - Riska Alvarido; Rika Lidyah (Takaza Innovatix Labs Ltd., 2026)
The digital era has brought significant transformations to Islamic finance through fintech, blockchain, and digital currencies, offering efficient, transparent, and inclusive innovations, but facing regulatory and Sharia compliance challenges. This research aims to analyze the digitalization of Islamic finance in the 5.0 era, provide a systematic review, and address the challenges of strengthening the halal ecosystem. The descriptive-analytical qualitative method was applied through library research with secondary data from 32 peer-reviewed journal articles (2020–2025) via PRISMA, analyzed thematically to map the themes of innovation, regulation, and sharia ethics. The results show the rapid development of Islamic fintech (P2P lending, halal crowdfunding), the main challenges are the absence of global regulatory standards and data security, as well as strengthening strategies through stakeholder collaboration and integration of maqashid sharia. It is concluded that adaptive regulations and digital education are needed to realize a sustainable Islamic financial ecosystem in the 5.0 era.